The Environment in the eyes of the people and the press - Chi, Jovylyn Belle Y. 1979-
This study aims to analyze how newspapers treat/handle environmental issues/events, as well as to identify the editorial policies and to ascertain the receptivity of the Philippine Daily Inquirer and Philippine Star to environmental issues/events. The study also aims to know the perception and ascertain the awareness of a group of respondents towards environmental journalism. To achieve these objectives, the researcher content analyzed 48 issues of the Philippine Daily Inquirer (PDI) and the Philippine Star (Phil. Star) from December 1999 to May 2000. A total of 147 environmental articles of the PDI and 112 environmental articles of Phil. Star were analyzed. The researcher also conducted interviews with the editors of PDI and Phil. Star to ascertain their editorial policies and their receptivity to environmental issues or events. Three environmental journalists were also interviewed to learn about their experiences in writing about the environment and in being published by local newspapers. The study found that the PDI published more stories about toxic and hazardous wastes. Stories on marine life were minimal with only two articles found by the researcher in the period covered. The Philippine Star had the most number of articles about natural calamities and the least on conservation and preservation. Almost all of the environmental articles in the PDI and Phil. Star appeared in the inside and supplementary pages. These two papers treated the stories favorably. In the interviews with the editors of the PDI and Phil. Star, it was learned that environmental journalism is one of their priorities. The environmental journalists interviewed said that newspapers today are receptive to environmental issues and events. The survey revealed that respondents read environmental stories although majority of them read these kinds of stories only one to two times a month. All of the respondents thought that environmental journalism is important because it creates awareness among the people about what is happening in the environment.